Numerical Simulation And experimental Measurement Of pulse generation in coaxial Forming lines; IEEE International Conference on Plasma Science (ICOPS) - Pegel I. V. Igor Valerievich; Moreland L. D. Dmitrii; Roitman A. M.; Gunin A. V. Alexander Vladimirovich; Rostov V. V. Vladislav Vladimirovich; Schamiloglu E.; Gubanov V. P.; Korovin S. D.; Tarakanov V. P. (1994, 1994)
Title screen